2003
DOI: 10.1088/0264-9381/20/16/310
|View full text |Cite
|
Sign up to set email alerts
|

Boundary charges in gauge theories: using Stokes theorem in the bulk

Abstract: Boundary charges in gauge theories (like the ADM mass in general relativity) can be understood as integrals of linear conserved n-2 forms of the free theory obtained by linearization around the background. These forms are associated one-to-one to reducibility parameters of this background (like the time-like Killing vector of Minkowski space-time). In this paper, closed n-2 forms in the full interacting theory are constructed in terms of a one parameter family of solutions to the full equations of motion that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
216
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(221 citation statements)
references
References 39 publications
(136 reference statements)
5
216
0
Order By: Relevance
“…Here, we show that the integration of the surface form k ∂t,0 [δφ, φ] along a path γ in solution space [10,32],…”
Section: Application To Black Strings In Plane Wavesmentioning
confidence: 93%
See 2 more Smart Citations
“…Here, we show that the integration of the surface form k ∂t,0 [δφ, φ] along a path γ in solution space [10,32],…”
Section: Application To Black Strings In Plane Wavesmentioning
confidence: 93%
“…For additional properties of these surface charges, as the representation theorem of the Lie algebra of reducibility parameters, the reader is referred to the original work [9,10].…”
Section: Conservation Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…One should expect that a similar expression for Q(ξ) in Eq. (2.7) could also be found using covariant methods as in [10] The algebra of the charges (2.7) is identical to the standard one, namely AdS for D > 3 [6,7], and two copies of the Virasoro algebra with the same central extension for D = 3 [8]. This can be readily obtained following Ref [11], where it is shown that the bracket of two charges provides a realization of the asymptotic symmetry algebra with a possible central extension.…”
Section: Introductionmentioning
confidence: 89%
“…Our starting point is the covariant approach to surface charges and their algebra developed in [10] (see also [11,12]). In particular, for pure Einstein gravity with or without a cosmological constant, it has been shown in [13] that for the linearized theory, described by h µν around a background g µν , the conserved surface charges are completely classified by the Killing vectors ξ µ of the metric g µν .…”
Section: General Expressions For Surface Charge One-forms From Linearmentioning
confidence: 99%